2021
DOI: 10.1002/jbio.202000461
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric evaluation of hemolysis in plasma by quantification of free oxyhemoglobin, methemoglobin, and methemalbumin in presence of bilirubin

Abstract: Severe intravascular hemolysis leads to the simultaneous presence of free heme pigments (oxyhemoglobin, methemoglobin, and methemalbumin) and bilirubin in human plasma. Standard spectrophotometric methods used to assess in vivo hemolysis inadequately address this complex analytical situation. Thus, we propose a novel quantification algorithm to ensure the highest analytical specificity. A corresponding second-derivative fitting algorithm was validated according to the guideline of bioanalytical method validati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Representative UV-VIS spectra peaks for met-Hb and oxy-Hb were observed at ∼406 and ∼412 nm, respectively [ 60 , 61 ]. Similarly, our Hb 6 μGel and ascorbic acid-reduced Hb 6 μGel (presumably oxygenated Hb μGel) had UV-VIS spectral peaks at ∼408 and ∼413 nm, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Representative UV-VIS spectra peaks for met-Hb and oxy-Hb were observed at ∼406 and ∼412 nm, respectively [ 60 , 61 ]. Similarly, our Hb 6 μGel and ascorbic acid-reduced Hb 6 μGel (presumably oxygenated Hb μGel) had UV-VIS spectral peaks at ∼408 and ∼413 nm, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, recent studies on haemolysis focus on developing and improving absorbance methods by measurement of few different wavelengths and additional mathematical algorithm for interference determination and elimination. Increasing number of reports on lysis quantification in blood sample have confirmed the effectiveness of using absorbance-based method improved by mathematical algorithm 22 , 23 , 33 35 . Interestingly, we have also shown that usage of the entire absorbance spectrum for the samples to evaluate haemolysis could be a viable alternative method that would not rely on a priori selection of important wavelengths (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 96%
“…One possible explanation for these findings is that hemolysis can elevate MetHb levels. In fact, studies reported that methemoglobinemia originated from intravascular hemolysis 18 and observed in-bag hemolysis of stored RBCs due to oxidative stress. 19,20 The difference in MetHb level between both groups was minimal, and the predictive ability for hemolysis was not excellent; however, MetHb elevation could be due to hemolysis during CPB.…”
Section: Discussionmentioning
confidence: 99%
“…During hemolysis, hemoglobin is released into the circulation as oxyhemoglobin, which is expected to be oxidized to MetHb. Studies have reported methemoglobinemia caused by intravascular hemolysis 18 and in-bag hemolysis of stored red blood cells (RBCs) due to oxidative stress. 19,20…”
mentioning
confidence: 99%
See 1 more Smart Citation